Баруун монголд “хувьсгал” авчирсан эрхэм - Нацов (Сирен Арабдынович) - Г, Ариунболд (Journal of International Studies, 2009)
English title: Sir who brought “Revolution” to Western Mongolia - Natsov (Siren Arabdinovich)